2015
DOI: 10.17512/jamcm.2015.4.13
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the core orthotropy on the wrinkling of sandwich panels

Abstract: Abstract. The paper concerns the phenomenon of wrinkling of compressed facing of a sandwich panel. The parametric analysis of the numerical model of the sandwich panel with a soft core is presented. The core was assumed as an elastic orthotropic material. The results of numerical simulations show the sensitivity of a sandwich structure to the variations of the core parameters. The results are evaluated qualitatively and quantitatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Analysing the results of LPF factor, column 2 in Table 3 - Example 1(b-d), it can be concluded that lower value of foam's E causes faster local instability of the compressed face. Similar observations have been made in the paper [10].…”
Section: Fig 2 Fe Solutions For Panel Without Openingssupporting
confidence: 91%
“…Analysing the results of LPF factor, column 2 in Table 3 - Example 1(b-d), it can be concluded that lower value of foam's E causes faster local instability of the compressed face. Similar observations have been made in the paper [10].…”
Section: Fig 2 Fe Solutions For Panel Without Openingssupporting
confidence: 91%
“…The regular hexagonal cell systems have different properties if we apply load (or forced displacement) in another direction. The anisotropy of the structure highly influences the structural behavior of mechanical systems [8]. In the 9c_c model, the boundary conditions have been changed.…”
Section: Resultsmentioning
confidence: 99%
“…The problem discussed in this paper is close to the issues of local instability of slender shell resting on an elastic foundation [10]. It is also worth noting that the problems of instability very frequently are characterized by high sensitivity due to the parameters of the considered system [11].…”
Section: Introductionmentioning
confidence: 83%